A method for preparing carbon slurry with interface repairing ability and its application

By using isopropanol as a solvent and alkyl ammonium iodide molecule repair interface in carbon-based perovskite solar cells, the corrosion problem of carbon slurry solvent on the perovskite active layer is solved, and the photoelectric conversion efficiency and humidity stability of carbon-based perovskite solar cells are improved.

CN116525176BActive Publication Date: 2025-03-11CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310435959.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2025-03-11
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

In planar structure carbon-based perovskite solar cells, the solvent in the carbon slurry corrodes the perovskite active layer material, destroying the perovskite active layer structure, weakening the physical contact of the "carbon electrode/perovskite active layer" interface, and hindering the improvement of photoelectric conversion efficiency.

Method used

Isopropanol is used as a solvent to mix the carbon powder with carbon powder, and alkyl ammonium iodide molecules are added to the carbon slurry for doping activation. The coordination effect of the alkyl ammonium iodide molecule and the surface of carbon particles and the passivation effect of the perovskite active layer repaired the perovskite active layer/carbon electrode interface.

Benefits of technology

It effectively reduces the corrosion effect of carbon slurry solvent on perovskites, improves the hydrophobicity and stability of carbon electrodes, repairs interface defects, improves the photoelectric conversion efficiency of planar structure carbon-based perovskite solar cells to more than 19%, and improves humidity stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004192332620000011
    Figure HDA0004192332620000011
  • Figure HDA0004192332620000021
    Figure HDA0004192332620000021
  • Figure HDA0004192332620000031
    Figure HDA0004192332620000031
Patent Text Reader

Abstract

The invention discloses a method for preparing a carbon slurry with interface repairing ability and its application, characterized in that an inert solvent isopropanol is used as a carbon slurry solvent, and alkyl ammonium iodide molecules are used to perform doping and activation treatment on the carbon slurry. The novel carbon slurry can be used for the top electrode of a planar carbon-based perovskite solar cell. Alkyl ammonium iodide molecule doping can improve the work function of the carbon electrode. After the carbon slurry is deposited on the perovskite active layer, the alkyl ammonium iodide molecules react with the surface of the perovskite active layer to form a 2D phase, passivate the surface defects of the active layer, thereby achieving a repair effect on the "perovskite / carbon electrode" interface and improving the photoelectric conversion efficiency of the planar carbon-based perovskite solar cell. At the same time, due to the hydrophobicity of the alkyl chain, the carbon slurry can greatly improve the humidity resistance stability of the device. The method has a wide range of application prospects in perovskite photoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of optoelectronic devices, and more specifically relates to a preparation method of a carbon slurry with "interface repair ability" and its application in a planar structure carbon-based perovskite solar cell. Technical Background

[0002] The photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells has increased rapidly, and its photoelectric conversion efficiency has climbed to 25.7%, which has attracted widespread attention and become a strong candidate for the next generation of photovoltaic technology. However, such perovskite solar cells usually use expensive materials such as Spiro-OMeTAD, PTAA, and P3HT as hole transport layers, and need to evaporate precious metals such as Au and Ag as top electrodes under a vacuum environment, which increases the preparation cost of the device. In addition, due to the corrosiveness of organic-inorganic hybrid perovskite materials to metal electrodes, the stability of the device is challenged. Carbon electrodes have excellent conductivity and corrosion resistance, and have a more suitable work function, becoming an effective alternative to metal top electrodes. After substitution, the stability problem caused by corrosion can be effectively solved. Moreover, the graphite and carbon black materials that constitute the carbon film are inexpensive, which can reduce the cost of the device. For this reason, perovskite solar cells based on carbon electrodes (i.e., carbon-based perovskite solar cells) have become an important branch in this field. The typical device structures of this branch include mesoporous structures, embedded structures, planar and quasi-planar structures. The planar carbon-based perovskite solar cell consists of a conductive substrate, an electron transport layer, a perovskite active layer and a carbon electrode, presenting a simple sandwich structure, which has the advantages of simple structure, low cost and good stability. However, during the device preparation process, the solvent in the carbon slurry corrodes the perovskite active layer material, destroys the perovskite active layer structure, weakens the physical contact of the "carbon electrode / perovskite active layer" interface, and seriously hinders the improvement of the photoelectric conversion efficiency of the structure device. Coupled with the interface energy level mismatch and interface defect problems, the photoelectric conversion efficiency of carbon-based perovskite devices has long lagged behind that of metal electrode devices. For example, the highest efficiency reported so far is 18.9% [see reference: Ye, T., et al., Cost-Effective High-Performance Charge-Carrier-Transport-Layer-Free Perovskite Solar Cells Achieved by Suppressing Ion Migration. ACS Energy Letters, 2021, 6: p.3044-3052], which is far from the metal electrode perovskite solar cell (25.7%) [https: / / www.nrel.gov / pv / cell-efficiency.html]. Therefore, repairing the "perovskite active layer / carbon electrode" interface is a key issue in this field.

[0003] To address this problem, solvent replacement, device post-annealing and other methods are usually used in the field. These strategies have improved the photoelectric conversion efficiency of planar carbon-based perovskite solar cells to a certain extent, but the degree of improvement is limited. To this end, the present invention takes a different approach and proposes an effective solution to the above problem: using isopropanol as a solvent and mixing it with carbon powder to prepare carbon paste, and at the same time using alkyl ammonium iodide molecules to dope and activate the carbon paste. This new carbon paste can be used to prepare carbon electrodes and used as the top electrode of planar carbon-based perovskite solar cells.

[0004] The beneficial features of the invention are as follows: 1. Isopropanol has an inert characteristic and has a very weak dissolution and destruction effect on perovskite materials, which is beneficial to reduce the corrosion of carbon slurry solvents on perovskites; 2. Alkyl ammonium iodide molecules can improve the hydrophobicity of carbon electrodes, thereby improving the overall stability of carbon-based perovskite solar cells; 3. Alkyl ammonium iodide molecules in carbon slurry react with lead halide perovskite active layers to generate 2D phase structures, achieving surface passivation of the perovskite active layer and repair of the "perovskite / carbon electrode" interface; 4. Alkyl ammonium iodide molecule doping can increase the work function of the carbon electrode to more than 5.0 eV, improve the charge transfer at the "perovskite / carbon electrode" interface, inhibit recombination, and increase the device efficiency of planar structure carbon-based perovskite solar cells to more than 19%. In summary, the technical solution of the invention can simultaneously improve the photoelectric conversion efficiency and humidity stability of planar structure carbon-based perovskite solar cells. Summary of the invention

[0005] The present invention provides a method for preparing a carbon slurry with interface repairing ability, that is, isopropyl alcohol is used as a solvent to prepare the carbon slurry, and alkyl ammonium iodide molecules are used to dope and activate the carbon slurry, and the coordination effect between the alkyl ammonium iodide molecules and the surface of carbon particles and the passivation effect between the alkyl ammonium iodide molecules and the active surface of perovskite are utilized to repair the perovskite active layer / carbon electrode interface, thereby improving the photoelectric conversion efficiency and stability of a planar structure carbon-based perovskite solar cell.

[0006] The invention provides a method for preparing a carbon slurry with interface repairing ability, which is characterized by using isopropyl alcohol as a solvent and mixing it with carbon powder, alkyl ammonium iodide and an adhesive to prepare the carbon slurry.

[0007] A method for preparing a carbon slurry having an interface repairing ability comprises the following steps:

[0008] 25 ml of isopropanol was selected as the solvent, and graphite powder, carbon black, cellulose, and an appropriate amount of alkyl ammonium iodide were added and ball-milled for 24 hours to prepare the product.

[0009] The alkylammonium iodide is preferably butylammonium iodide (C4H 12IN, referred to as BAI), octyl ammonium iodide (C8H 20 IN, referred to as OAI), iodine amine (C 10 H 24 IN, referred to as DAI), dodecyl ammonium iodide (C 12 H 28 IN), phenethylamine iodide (C8H 12 IN, referred to as PEAI).

[0010] The carbon powder is a combination of carbon black and graphite.

[0011] The adhesive is preferably hydroxypropyl cellulose.

[0012] The mass ratio of the alkyl iodide amine molecules to the carbon powder is in the range of 1% to 6%.

[0013] An application of carbon paste with interface repair ability is characterized by coating the carbon paste on the perovskite active layer to prepare a carbon electrode and a planar structure carbon-based perovskite solar cell.

[0014] The molecular formula of the perovskite is abbreviated as ABX3, wherein A is a combination of methylamine ion and formamidine ion; B is a lead ion; and X is a halogen ion, which is a combination of chloride ion, bromide ion and iodine ion.

[0015] The coating method is any one of blade coating, slit coating and screen printing.

[0016] The carbon electrode needs to be annealed during the preparation process. The annealing environment is the atmospheric environment. The temperature range is 60 to 120° C. and the annealing time is 5 to 60 minutes.

[0017] The work function of the carbon electrode can be increased to above 5.0 eV.

[0018] The carbon electrode has good hydrophobicity.

[0019] An application of a carbon slurry with interface repair ability, that is, an application method in a planar structure carbon-based perovskite solar cell, comprises the following steps:

[0020] 1) Preparation of SnO2 layer: SnO2 quantum dots are coated on the substrate into a thin film, and then annealed at 150°C for 60 minutes.

[0021] 2) PbI2: Prepare PbI2 solution, apply it into a thin film on the SnO2 substrate, and dry it.

[0022] 3) Organic ion salt deposition: Prepare an organic ion salt solution, coat it into a thin film on a PbI2 substrate, and anneal it in air at 145°C for 20 minutes.

[0023] 4) Preparation of carbon electrode: The carbon electrode components are a combination of conductive carbon black, graphite, and hydroxypropyl cellulose; the solvent is isopropyl alcohol; the additive is one of BAI, OAI, DAI, dodecyl ammonium iodide, and PEAI; ball milling is used for blending; and the carbon slurry is coated on the perovskite film to prepare the carbon electrode.

[0024] 5) Annealing and drying: annealing the film assembled in the above order at 50° C. to 160° C. for 5 to 60 minutes in an atmospheric environment, and drying to obtain a carbon electrode, thereby obtaining the planar structure carbon-based perovskite solar cell.

[0025] Compared with the prior art, the beneficial technical effects of the present invention are:

[0026] 1) Isopropyl alcohol is used as the solvent to minimize the corrosion of the carbon slurry solvent on the perovskite.

[0027] 2) The addition of alkylammonium iodide molecules can increase the work function of the carbon electrode.

[0028] 3) The addition of alkylammonium iodide molecules can promote the formation of two-dimensional structured perovskite at the interface between the perovskite active layer and the carbon electrode, passivate the defects of the perovskite / carbon electrode interface, and realize the interface repair function.

[0029] 4) The addition of alkylammonium iodide molecules can provide hydrophobicity to the carbon electrode and improve the humidity stability of the device.

[0030] 5) The combination of the above advantages can increase the photoelectric conversion efficiency of planar carbon-based perovskite solar cells to more than 19%, and enable the device to obtain excellent humidity stability without packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a work function test of the carbon electrode prepared in Example 1 of the present invention.

[0032] Figure 2 This is a water contact angle test of the carbon electrode prepared in Example 1 of the present invention.

[0033] Figure 3 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 2 of the present invention.

[0034] Figure 4 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 3 of the present invention.

[0035] Figure 5 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 4 of the present invention.

[0036] Figure 6 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 5 of the present invention.

[0037] Figure 7 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 6 of the present invention.

[0038] Figure 8 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 7 of the present invention.

[0039] Fig. 9 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 8 of the present invention.

[0040] Fig.10 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 9 of the present invention.

[0041] Fig.11 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 10 of the present invention.

[0042] Fig.12 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 11 of the present invention.

[0043] Fig.13 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 12 of the present invention.

[0044] Fig.14 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 13 of the present invention.

[0045] Fig.15 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 14 of the present invention.

[0046] Fig.16 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 15 of the present invention.

[0047] Fig.17 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 16 of the present invention.

[0048] Fig.18 This is the photocurrent-voltage curve of the planar structure carbon-based perovskite solar cell prepared in Example 17 of the present invention. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0050] The present invention will be further described below in conjunction with specific embodiments and drawings.

[0051] Embodiment 1:

[0052] 1) Preparation of carbon slurry: Conductive carbon black (0.85 g), graphite (5 g), hydroxypropyl cellulose (1 g), and alkyl ammonium iodide (170 mg) were weighed and put into a ball mill, and 25 ml of isopropanol was added and ball milled for 24 h to obtain a carbon slurry.

[0053] 2) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of a glass substrate and anneal at 100°C for 10 min in air to solidify the carbon electrode.

[0054] After the carbon electrode of Example 1 is prepared, the work function measured by ultraviolet photoelectron spectroscopy is shown in the figure ( Figure 1 ), and a work function of 5.09 eV was obtained; the water contact angle of the carbon electrode is shown in the figure ( Figure 2 ), a water contact angle greater than 60° can be obtained.

[0055] Embodiment 2:

[0056] 1) Preparation of carbon slurry: Conductive carbon black (0.85 g), graphite (5 g), and hydroxypropyl cellulose (1 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added and ball milled for 24 h to obtain a carbon slurry.

[0057] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0058] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0059] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 100°C for 10 min in air to solidify the carbon electrode.

[0060] After the planar carbon-based perovskite solar cell device of Example 2 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Figure 3 ), and achieved a photoelectric conversion efficiency of 10.26%.

[0061] Embodiment 3:

[0062] 1) Preparation of carbon slurry: Conductive carbon black (0.72 g), graphite (9.2 g), hydroxypropyl cellulose (0.5 g), and BAI (0.1 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of BAI (alkyl ammonium iodide) to carbon powder was 1%.

[0063] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0064] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0065] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal in air at 60°C for 60 min to solidify to form a carbon electrode.

[0066] After the planar carbon-based perovskite solar cell device of Example 3 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Figure 4 ), and achieved a photoelectric conversion efficiency of 11.02%.

[0067] Embodiment 4:

[0068] 1) Preparation of carbon slurry: Conductive carbon black (0.75 g), graphite (6 g), hydroxypropyl cellulose (0.6 g), and BAI (0.2 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of BAI (alkyl ammonium iodide) to carbon powder was 3%.

[0069] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0070] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0071] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 90°C for 30 minutes in air to solidify the carbon electrode.

[0072] After the planar carbon-based perovskite solar cell device of Example 4 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Figure 5 ), and a photoelectric conversion efficiency of 16.27% was obtained.

[0073] Embodiment 5:

[0074] 1) Preparation of carbon slurry: Conductive carbon black (0.76 g), graphite (5.9 g), hydroxypropyl cellulose (0.65 g), and BAI (0.4 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of BAI (alkyl ammonium iodide) to carbon powder was 6%.

[0075] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0076] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0077] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 120°C for 5 minutes in air to solidify the carbon electrode.

[0078] After the planar carbon-based perovskite solar cell device of Example 5 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Figure 6 ), and achieved a photoelectric conversion efficiency of 15.53%.

[0079] Embodiment 6:

[0080] 1) Preparation of carbon slurry: Conductive carbon black (0.4 g), graphite (4.5 g), hydroxypropyl cellulose (0.77 g), and OAI (0.049 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added and ball milled for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of OAI (alkyl ammonium iodide) to carbon powder was 1%.

[0081] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0082] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0083] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 600°C for 60 minutes in air to solidify the carbon electrode.

[0084] After the planar carbon-based perovskite solar cell device of Example 6 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Figure 7 ), and achieved a photoelectric conversion efficiency of 14.60%.

[0085] Embodiment 7:

[0086] 1) Preparation of carbon slurry: Conductive carbon black (0.48 g), graphite (5.6 g), hydroxypropyl cellulose (0.77 g), and OAI (0.18 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added and ball milled for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of OAI (alkyl ammonium iodide) to carbon powder was 3%.

[0087] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0088] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0089] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 90°C for 30 minutes in air to solidify the carbon electrode.

[0090] After the planar carbon-based perovskite solar cell device of Example 7 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Figure 8 ), and achieved a photoelectric conversion efficiency of 19.58%.

[0091] Embodiment 8:

[0092] 1) Preparation of carbon slurry: Conductive carbon black (0.92 g), graphite (7.4 g), hydroxypropyl cellulose (0.77 g), and OAI (0.5 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added and ball milled for 24 hours to disperse uniformly to obtain carbon slurry. The mass ratio of OAI (alkyl ammonium iodide) to carbon powder was 6%.

[0093] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0094] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0095] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 120°C for 5 minutes in air to solidify the carbon electrode.

[0096] After the planar carbon-based perovskite solar cell device of Example 8 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig. 9 ), and achieved a photoelectric conversion efficiency of 17.15%.

[0097] Embodiment 9:

[0098] 1) Preparation of carbon slurry: Conductive carbon black (0.35 g), graphite (8.2 g), hydroxypropyl cellulose (0.9 g), and DAI (0.085 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of DAI (alkyl ammonium iodide) to carbon powder was 1%.

[0099] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0100] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0101] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal in air at 60°C for 60 min to solidify to form a carbon electrode.

[0102] After the planar carbon-based perovskite solar cell device of Example 9 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.10 ), and achieved a photoelectric conversion efficiency of 10.28%.

[0103] Embodiment 10:

[0104] 1) Preparation of carbon slurry: Conductive carbon black (0.52 g), graphite (7.4 g), hydroxypropyl cellulose (0.9 g), and DAI (0.237 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of DAI (alkyl ammonium iodide) to carbon powder was 3%.

[0105] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0106] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0107] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 90°C for 30 minutes in air to solidify the carbon electrode.

[0108] After the planar carbon-based perovskite solar cell device of Example 10 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.11 ), and a photoelectric conversion efficiency of 17.90% was obtained.

[0109] Embodiment 11:

[0110] 1) Preparation of carbon slurry: Conductive carbon black (0.63 g), graphite (5.4 g), hydroxypropyl cellulose (0.9 g), and DAI (0.36 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of DAI (alkyl ammonium iodide) to carbon powder was 6%.

[0111] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0112] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0113] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 120°C for 5 minutes in air to solidify the carbon electrode.

[0114] After the planar carbon-based perovskite solar cell device of Example 11 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.12 ), and achieved a photoelectric conversion efficiency of 16.86%.

[0115] Embodiment 12:

[0116] 1) Preparation of carbon slurry: Conductive carbon black (0.5 g), graphite (1.5 g), hydroxypropyl cellulose (1 g), and dodecyl ammonium iodide (0.02 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of dodecyl ammonium iodide (alkyl ammonium iodide) to carbon powder was 1%.

[0117] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0118] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0119] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal in air at 60°C for 60 min to solidify to form a carbon electrode.

[0120] After the planar carbon-based perovskite solar cell device of Example 12 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.13 ), and achieved a photoelectric conversion efficiency of 15.26%.

[0121] Embodiment 13:

[0122] 1) Preparation of carbon slurry: Conductive carbon black (0.55 g), graphite (4.1 g), hydroxypropyl cellulose (0.96 g), and dodecyl ammonium iodide (0.14 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of dodecyl ammonium iodide (alkyl ammonium iodide) to carbon powder was 3%.

[0123] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0124] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0125] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 90°C for 30 minutes in air to solidify the carbon electrode.

[0126] After the planar carbon-based perovskite solar cell device of Example 13 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.14 ), and achieved a photoelectric conversion efficiency of 18.02%.

[0127] Embodiment 14:

[0128] 1) Preparation of carbon slurry: Conductive carbon black (0.58 g), graphite (4.45 g), hydroxypropyl cellulose (0.54 g), and dodecyl ammonium iodide (0.3 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of dodecyl ammonium iodide (alkyl ammonium iodide) to carbon powder was 6%.

[0129] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0130] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0131] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 120°C for 5 minutes in air to solidify the carbon electrode.

[0132] After the planar carbon-based perovskite solar cell device of Example 14 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.15 ), and achieved a photoelectric conversion efficiency of 17.53%.

[0133] Embodiment 15:

[0134] 1) Preparation of carbon slurry: Conductive carbon black (1.1 g), graphite (2.1 g), hydroxypropyl cellulose (1 g), and PEAI (0.032 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of PEAI (alkyl ammonium iodide) to carbon powder was 1%.

[0135] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0136] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0137] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal in air at 60°C for 60 min to solidify to form a carbon electrode.

[0138] After the planar carbon-based perovskite solar cell device of Example 15 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.16), achieving a photoelectric conversion efficiency of 10.99%.

[0139] Embodiment 16:

[0140] 1) Preparation of carbon slurry: Conductive carbon black (0.98 g), graphite (4.5 g), hydroxypropyl cellulose (1 g), and PEAI (0.16 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of PEAI (alkyl ammonium iodide) to carbon powder was 3%.

[0141] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0142] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0143] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 90°C for 30 minutes in air to solidify the carbon electrode.

[0144] After the planar carbon-based perovskite solar cell device of Example 16 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.17 ), and achieved a photoelectric conversion efficiency of 17.36%.

[0145] Embodiment 17:

[0146] 1) Preparation of carbon slurry: Conductive carbon black (0.83 g), graphite (4.8 g), hydroxypropyl cellulose (1 g), and PEAI (0.34 g) were weighed and added into a ball mill, and 25 ml of isopropanol was added to ball mill for 24 hours to disperse evenly to obtain carbon slurry. The mass ratio of PEAI (alkyl ammonium iodide) to carbon powder was 6%.

[0147] 2) Preparation of SnO2 electron transport layer: SnO2 QDs were spin-coated on the fluorine-doped tin oxide (FTO) surface and annealed at 150°C for 60 min in air to form a dense SnO2 electron transport layer.

[0148] 3) Preparation of perovskite active layer: PbI2 solution was coated on the substrate prepared in step 2) in a glove box and dried at 70°C; then, an organic ion solution (FAI / MACl / MABr) was deposited on this basis, transferred to air, and annealed at 145°C for 20 minutes to form a perovskite active layer.

[0149] 4) Preparation of carbon electrode: Apply an appropriate amount of carbon slurry on the surface of the perovskite active layer by scraping, and anneal at 120°C for 5 minutes in air to solidify the carbon electrode.

[0150] After the planar carbon-based perovskite solar cell device of Example 17 was prepared, at 100 mW / cm 2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.18 ), and achieved a photoelectric conversion efficiency of 16.62%.

Claims

1. A method for preparing a carbon slurry having the ability to repair the interface between a perovskite active layer and a carbon electrode, characterized in that: Isopropyl alcohol is used as a solvent to mix with carbon powder, alkyl ammonium iodide molecules and a binder to prepare carbon paste.

2. The method for preparing a carbon slurry having the ability to repair the interface between the perovskite active layer and the carbon electrode according to claim 1, characterized in that: The alkylammonium iodide molecule is one of butylammonium iodide, octylammonium iodide, quinoline iodide, dodecylammonium iodide, and phenethylammonium iodide.

3. The method for preparing a carbon slurry having the ability to repair the interface between the perovskite active layer and the carbon electrode according to claim 1, characterized in that: The mass ratio of alkyl ammonium iodide molecules to carbon powder is in the range of 1% to 6%.

4. Application of a carbon slurry having the ability to repair the interface between a perovskite active layer and a carbon electrode, characterized in that: The carbon paste according to any one of claims 1 to 3 is coated on the perovskite active layer to prepare a carbon electrode, and a planar structure carbon-based perovskite solar cell is prepared.

5. The use of a carbon slurry having the ability to repair the interface between the perovskite active layer and the carbon electrode as claimed in claim 4, characterized in that: The molecular formula of perovskite is abbreviated as ABX3, where A is methylamine ion, formamidine ion or a combination of the two, B is lead ion, and X is halogen ion.

6. The use of a carbon slurry having the ability to repair the interface between the perovskite active layer and the carbon electrode as claimed in claim 4, characterized in that: The carbon electrode needs to be annealed during the preparation process. The annealing environment is the atmospheric environment, the temperature range is 60 to 120°C, and the annealing time is 5 to 60 minutes.

7. The use of a carbon slurry having the ability to repair the interface between the perovskite active layer and the carbon electrode as claimed in claim 4, characterized in that: The work function of the carbon electrode is increased to above 5.0 eV.

8. A method for preparing a planar carbon-based perovskite solar cell, characterized in that: The following steps are involved: 1) Preparation of SnO2 layer: SnO2 quantum dots are coated on the substrate into a thin film, and then annealed at 150°C for 60 minutes; 2) PbI2: Prepare PbI2 solution, apply it into a thin film on SnO2 substrate, and dry it; 3) Organic ion salt deposition: prepare an organic ion salt solution, coat it on a PbI2 substrate to form a thin film, and anneal it in air at 145°C for 20 minutes; 4) Preparation of carbon electrode: coating the carbon paste described in any one of claims 1 to 3 on the perovskite film, and then annealing at 60° C. to 120° C. for 5 to 60 minutes in an atmospheric environment, solidifying to obtain a carbon electrode, and obtaining a planar structure carbon-based perovskite solar cell.

9. A planar carbon-based perovskite solar cell, characterized in that: Prepared according to the preparation method of claim 8, or coating the carbon paste of any one of claims 1-3 on the perovskite active layer to prepare a carbon electrode, and prepare a planar structure carbon-based perovskite solar cell.

Citation Information

Patent Citations

  • Preparation method of carbon electrode perovskite solar cell

    CN111697140A

  • Perovskite solar cell and preparation method thereof

    CN114300621A

  • Preparation method of perovskite solar cell

    CN115172610A